2014
DOI: 10.1186/1476-4598-13-92
|View full text |Cite
|
Sign up to set email alerts
|

Lnc RNA HOTAIR functions as a competing endogenous RNA to regulate HER2 expression by sponging miR-331-3p in gastric cancer

Abstract: BackgroundAccumulating evidence indicates that the long non-coding RNA HOTAIR plays a critical role in cancer progression and metastasis. However, the overall biological role and clinical significance of HOTAIR in gastric carcinogenesis remains largely unknown.MethodsHOTAIR expression was measured in 78 paired cancerous and noncancerous tissue samples by real-time PCR. The effects of HOTAIR on gastric cancer cells were studied by overexpression and RNA interference approaches in vitro and in vivo. Insights of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
702
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(735 citation statements)
references
References 38 publications
22
702
0
Order By: Relevance
“…As confirmed by situ hybridization assay, HOTAIR was distributed in both nucleus and cytoplasm 33 , and has been reported to be able to bind miRNAs in cancers. 31,34 In this study, it was found that loss of DNMT3b inhibited HOTAIR-induced PTEN methylation. In addition, lack of the miR-29b binding site in HOTAIR prevented the suppression of miR-29b expression.…”
Section: Discussionmentioning
confidence: 68%
“…As confirmed by situ hybridization assay, HOTAIR was distributed in both nucleus and cytoplasm 33 , and has been reported to be able to bind miRNAs in cancers. 31,34 In this study, it was found that loss of DNMT3b inhibited HOTAIR-induced PTEN methylation. In addition, lack of the miR-29b binding site in HOTAIR prevented the suppression of miR-29b expression.…”
Section: Discussionmentioning
confidence: 68%
“…To stably silence endogenous HOTAIR, two shRNA oligonucleotides were purchased from Sigma Aldrich (Shanghai, China), and the oligonucleotides were as follows: shHOTAIR-I: 5′-CACCGCCTTTGCTTCGTGCTGATTCCGAAGAATCAG CACGAAGCAAAGGC-3′ and 5′-AAAAGCCTTTGCTTCGT GCTGATTCTTCGGAATCAGCACACGAAGCAAAGGC-3′; 11 shHOTAIR-II: 5′-GATCCCGAACGGGAGTACAGAGAGATT CAAGAGATCTCTCTGTACTCCCGTTCTTTTTTGGAAA-3′ and 5′-CGCGTTTCCAAAAAAGAACGGGAGTACAGAGAG ATCTCTTGAATCTCTCTGTACTCCCGTTCGG-3′; 12 they were cloned into the pGCSi-neo-GFP vector to generate pGCSi-neo-GFP-HOTAIR-RNAi(s). SCLC cells were transfected with shRNA via Lipofectamine 2000 (Invitrogen).…”
Section: Cell Culturementioning
confidence: 99%
“…9 In NSCLC, SULF2 and IGFBP-3 have also been observed to affect drug sensitivity of NSCLC cells. [10][11][12] The HOX family, including 39 HOX genes, is divided into four groups (A-D) in tightly linked clusters on different chromosomes, and has the equivalent position in each cluster. HOXA1, one of the HOX family members, has been reported to be involved in many important biological processes including cell growth, apoptosis, transformation, and survival.…”
mentioning
confidence: 99%
“…In GC, HOTAIR-expressing GC cells exhibited an enhanced ability of metastasis and peritoneal dissemination in a nude mouse model [57]. Liu et al confirmed that HOTAIR was markedly increased in GC tissues compared with matched normal tissues, and its loss led to suppressed proliferation of GC cells in vitro and in vivo.The investigation of the molecular mechanism revealed that HOTAIR indirectly regulated human epithelial growth factor receptor 2 (HER2) by competitively binding to miR-331-3p [58]. In addition, the plasma levels of HOTAIR were increased in the patients with GC compared with the healthy controls [52], suggesting that HOTAIR may be a noninvasive biomarker for GC diagnosis.…”
Section: Hotairmentioning
confidence: 99%